2019
DOI: 10.1111/tme.12604
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fibrinogen supplementation on clot formation in blood samples from cardiac surgery patients before and after tranexamic acid administration

Abstract: Summary Objectives To investigate if supplementation with fibrinogen concentrate to blood samples collected after tranexamic acid administration improve clot formation more than what can be achieved with fibrinogen in the absence of tranexamic acid. Background It is not known if the combination of fibrinogen and tranexamic acid has additional effects than what can be achieved individually. Methods Four blood samples were collected from 15 coronary artery bypass patients. Two samples were collected before surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…We could not determine the specific contribution of fibrinogen to haemostatic tests due to its interaction with tranexamic acid. A recent in‐vitro study suggested that tranexamic acid does not enhance the effects of fibrinogen on clot firmness in cardiac surgery, leaving it possible that tranexamic acid might interfere with fibrinogen’s effect [30]. Further research can help determine whether our results are replicable in general populations undergoing scoliosis surgery.…”
Section: Discussionmentioning
confidence: 86%
“…We could not determine the specific contribution of fibrinogen to haemostatic tests due to its interaction with tranexamic acid. A recent in‐vitro study suggested that tranexamic acid does not enhance the effects of fibrinogen on clot firmness in cardiac surgery, leaving it possible that tranexamic acid might interfere with fibrinogen’s effect [30]. Further research can help determine whether our results are replicable in general populations undergoing scoliosis surgery.…”
Section: Discussionmentioning
confidence: 86%
“…17,25 The direct effect of TXA administration measured by thromboelastometry (ROTEM, Pentapharm GmBh Munich, Germany) resulted in a small reduction in median CT but there was no significant difference in MCF. 53 Monaco et al, 54 in a randomized controlled trial involving 100 patients undergoing elective open abdominal aortic aneurysm repair, reported a 20% reduction in intraoperative blood loss and a 33% reduction in postoperative blood loss during the first 24 hours, without any apparent increases in adverse events including thromboembolism and death caused by TXA treatment.…”
Section: Tranexamic Acid and Fibrinolysismentioning
confidence: 99%